(untitled) (TANMIYAT AL-RAFIDAIN, 2026)
This paper intentionally tried to showcase the role of blockchain technology in improving administrative transparency by showing how the current-day modern technology can be utilized to build new administrative systems and fulfill the principles of administrative transparency. In order to meet the objectives of the research, a questionnaire was developed as a major tool of collecting data. There were 50 questions in the questionnaire and the views of 246 people were collected in the most different manner. The study was descriptive and analytical in nature, and it involved a number of statistical and software tools. Frequencies, percentages, means, standard deviations, relative importance, reliability, internal consistency, and normality have been determined with the help of SPSS v26 statistical software. Correlation and impact relationships were examined by using the AMOS v24 statistical software. The findings all came up to the conclusion that the use of blockchain technology in administration systems can play a significant part in ensuring transparency in the university through the introduction of a solid and secure online database, better and more precise information, and greater accountability of various administrative tiers. The paper suggests the implementation of a full-scale digital strategy at the University of Mosul that should involve the implementation of blockchain technology. It includes blockchain technology in its administrative system to guarantee better performance of the institutions and smart management of the universities through integrity and transparency.